Blockade of the hedgehog pathway inhibits osteophyte formation in arthritis. Issue 3 (10th January 2012) - Ruiz-Heiland, Gisela; Horn, Angelika; Zerr, Pawel; Hofstetter, Willy; Baum, Wolfgang; Stock, Michael; Distler, Jörg H; Nimmerjahn, Falk; Schett, Georg; Zwerina, Jochen
Abstract : Background: Osteophyte formation is a common phenomenon in arthritis. Bone formation by endochondral ossification is considered a key pathophysiological process in the formation of osteophytes. Objective: To examine the hypothesis that inhibition of smoothened (Smo), a key component of the hedgehog pathway inhibits osteophyte formation as the hedgehog pathway mediates endochondral ossification. Methods: Arthritis was induced in 8-week-old C57/BL6 mice by serum transfer (K/BxN model). Mice were then treated by daily administration of either vehicle or LDE223, a specific small molecule inhibitor for Smo, over 2 weeks starting at the onset of disease. Clinical course of arthritis, histological and molecular changes of bone in the affected joints as well as systemic bone changes were assessed. Results: Serum transfer-induced arthritis led to severe osteophyte formation within 2 weeks of onset. Blockade of Smo inhibited hedgehog signalling in vivo and also significantly inhibited osteophyte formation, whereas the clinical and histopathological signs of arthritis were not affected. Also, systemic bone mass did not change. Smo inhibitor particularly blocked the formation of hypertrophic chondrocytes and collagen type X expression. Conclusions: The data indicate that blockade of hedgehog signalling by targeting Smo specifically inhibits osteophyte formation in arthritis without affecting inflammation and without eliciting bone destruction at the local and systemic level. Blockade of Smo may thus be considered as a strategy to specifically influence the periosteal bone response in arthritis associated with bone apposition.